Keyakinan akan Pemanasan Global dan Kesediaan untuk Membayar Wisata Premium, Peran mediasi dari Sikap Ekowisata (Studi Kasus di Destinasi Wisata Labuan Bajo) - Fanggidae, Jappy Parlindungan (Jurnal Ilmiah Pariwisata, 2022)
This research is motivated by the efforts of the Indonesian government to make Labuan Bajo a super premium tourist destination. In this regard, this study presents the readiness of Labuan Bajo as a super premium tourist destination that will sell tourist attractions at premium prices, from the tourists’ perspectives. The purpose of this study was to investigate the relationship between global warming beliefs and willingness to pay for premium tourism. Such a relationship is mediated by ecotourism attitudes. The tourism literature notes that tourists who have high environmental concerns tend to be willing to pay a premium price for ecotourism experiences. Therefore, this study discusses other factors that influence the willingness to pay a premium, namely the personality of tourists, in this case, the belief in global warming. This study uses a quantitative method where the data collected by questionnaires are analyzed using Structural Model Analysis (SEM) with the assistance of the SmartPLS 3.0 software. The results of this study indicate that the willingness to travel premium is influenced by the belief that global warming is mediated by ecotourism attitudes. It is recommended to tourism practitioners and the government who want to promote Labuan Bajo as premium tourism to highlight the global warming dimension in their tourism campaign. Keywords: Global Warming, Ecotourism Attitude, Paid Premium Tours